MODEL PROSES PRODUKSI KEMASAN BERBASIS OFFSET PRINTING - Novi Purnama Sari; Dianta Mustofa Kamal; Muhammad Asrol; Zulkarnain (Politeknik Negeri Jakarta, 2023)
The need for packaging is currently increasing, providing opportunities for the development of the packaging printing industry, especially offset printing-based printing. This study aims to analyze the flow of the production process in the offset printing industry that produces packaging. This study uses a descriptive qualitative method to analyze the running of the production process which consists of pre-print, print, and post-print. The results showed that the results of the packaging printing production process at each stage were strongly influenced by the previous stage.